2022
DOI: 10.3390/ma15175912
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of Human Cancellous Bone in Alveolar Bone under Uniaxial Compression and Creep Tests

Abstract: In the process of orthodontic treatment, the remodeling of cancellous bone in alveolar bone (in this paper, cancellous bone in alveolar bone is abbreviated as CBAB) is key to promoting tooth movement. Studying the mechanical behavior of CBAB is helpful to predict the displacement of teeth and achieve the best effect of orthodontic treatment. Three CBAB samples were cut from alveolar bone around the root apex of human teeth. A uniaxial compression test was used to study the transient elastic properties of CBAB.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Besides, it could be found that the equivalent stress and equivalent strain distributions were inconsistent when the jaw model was in the ultimate yielding state. For example, when the 3 mm jaw model was in the ultimate yielding state, the buccal and lingual cancellous bone at the root incision had already experienced equivalent stress continuity, but the equivalent strains were still distributed only in the super cial layers of the buccal and lingual cancellous bone; when the equivalent stress at the edge of the free cortical bone had already exceeded the shear strength, the corresponding equivalent strain exceeding the yield strength was not observed, which may be related to the phenomenon of "hysteresis" [17] in osteo-viscoelasticity, where the strain response lags behind the stress. It is worth noting that during bone expansion, the stresses and strains were more concentrated in the cancellous bone and external cortical bone located in the region of the root incision, as well as in the lower 1/3 of the buccal lamellae of the free cortical bone, which suggests that in some cases of thin cortical bone, as the force increases, the buccal lamellae breakage may be located in the lower 1/3 of the lamellae, in addition to occurring in the root incision location.…”
Section: Discussionmentioning
confidence: 98%
“…Besides, it could be found that the equivalent stress and equivalent strain distributions were inconsistent when the jaw model was in the ultimate yielding state. For example, when the 3 mm jaw model was in the ultimate yielding state, the buccal and lingual cancellous bone at the root incision had already experienced equivalent stress continuity, but the equivalent strains were still distributed only in the super cial layers of the buccal and lingual cancellous bone; when the equivalent stress at the edge of the free cortical bone had already exceeded the shear strength, the corresponding equivalent strain exceeding the yield strength was not observed, which may be related to the phenomenon of "hysteresis" [17] in osteo-viscoelasticity, where the strain response lags behind the stress. It is worth noting that during bone expansion, the stresses and strains were more concentrated in the cancellous bone and external cortical bone located in the region of the root incision, as well as in the lower 1/3 of the buccal lamellae of the free cortical bone, which suggests that in some cases of thin cortical bone, as the force increases, the buccal lamellae breakage may be located in the lower 1/3 of the lamellae, in addition to occurring in the root incision location.…”
Section: Discussionmentioning
confidence: 98%
“…Alveolar bone is divided into three parts: intrinsic alveolar bone, cancellous bone, and cortical bone [1]. Alveolar bone changes actively during orthodontic treatment, which is bone remodeling.…”
Section: Introductionmentioning
confidence: 99%